Mapping the Future of OAuth: Insights from the IETF WG - Bonfim, Michel; Santos, Marcelo; Braga, Julião (Anais do Workshop Pré-IETF (WPIETF); 2025: Anais do X Workshop Pré-IETF, 2025)
This paper provides a systematic overview and in-depth analysis of the key active Internet-Drafts within the Internet Engineering Task Force (IETF) OAuth Working Group (WG). By focusing on proposals that have achieved consensus (WG Call for Adoption), we identify the core trends shaping the future of the OAuth 2.0 protocol, with a strong emphasis on security enhancements, user privacy, and granular authorization.